Analysis of Difficulties and Motivation in Learning Arabic from a Psycholinguistic Perspective - Kaila Innes Ayu Pradita; Lili Musyafa’ah (Journal of Practice Learning and Educational Development, 2026)
This research discusses the difficulties and motivations of learning Arabic from a psycholinguistic perspective at Rumah Belajar Thaybah Surabaya. The main issue lies in the linguistic and psychological difficulties students face in listening, understanding, and comprehending the Arabic language. This research aims to find solutions to these obstacles and identify internal and external motivational factors. The method used is qualitative case study with data collection techniques thru interviews, observations, and documentation of ten female students. Data analysis was conducted using the Miles and Huberman model with triangulation validity testing. The research results show that psychological factors such as anxiety and low self-confidence have a significant impact on linguistic difficulties, while internal motivation and interactive learning methods play an important role in enhancing learning effectiveness.